Nilai-Nilai Pendidikan Karakter Dalam Surah Al-Baqarah - Dian Nirmala Sofi; Nurfadilah; Sofyani Dinillah (STIKes Ibnu Sina Ajibarang, 2024)
The phenomenon of character crisis is now increasingly experienced by various age groups, which causes discomfort in society. The Al-Quran, as a source of solutions to various problems, as contained in QS al-Baqarah verses 261-267, can be a way to overcome character crises and teach good character which includes religious, personal and social values. This research is qualitative in nature and uses the literature study method. The subject of this research is Al-Qur’anul Karim. Data collection techniques include data collection and classification; The final step of this process is to group the data according to the theory used in the research. The character education values ​​found in Surah Al-Baqarah verses 261-267 include: (1) religious values, (2) personal moral values, such as good habits and generosity, and (3) social care values , such as keeping your word and giving the best of yourself.